Organisational Capability on ICT Support And SMEs’ Performances in Malaysia - LUEN HER, YAP; BIN AHMAD, SHUHYMEE; HEE, HOE CHEE (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study is intended to investigate the Information and communication technology (ICT) support that affects small and medium enterprises’ (SMEs) performances in Malaysia, which are mediated by the organisational capability. There were 296 surveys that were collected, and then it’s done a reliability analysis, descriptive analysis, Pearson correlation analysis, multiple linear analysis, and hierarchical regression analysis. The results showed that the ICT support presented a positive relationship with SMEs performance by using the multiple regression analysis. Also the organisational capability became the full mediating role in the relationship between ICT support, and SMEs performance. RESUMEN Este estudio tiene como objetivo investigar el apoyo a las tecnologías de la información y las comunicaciones (TIC) que afecta el desempeño de las pequeñas y medianas empresas (PYMEs) en Malasia, las cuales están mediadas por la capacidad organizativa. Hubo 296 encuestas que fueron recolectadas y posteriormente se realiza un análisis de confiabilidad, análisis descriptivo, análisis de correlación de Pearson, análisis lineal múltiple y análisis de regresión jerárquica. Los resultados mostraron que el apoyo a las TIC presentó una relación positiva con el desempeño de las PYMEs al utilizar el análisis de regresión múltiple. Además, la capacidad organizativa se convirtió en mediadora de la relación entre el apoyo a las TIC y el desempeño de las PYMEs.